G Gambaran Upaya Deteksi Dini Dan Pencegahan Hipertensi Di Desa Kayu Bawang Di Wilayah Kerja Puskesmas Gambut - lukman harun; Mery Lestari; Hiryadi (LPPM Universitas Sari Mulia, 2022)
Background : Hypertension is a health problem that is not only intense in the world, but also in Indonesia. Hypertension is also referred to as the silent killer, which is a deadly disease without any signs and symptoms first as a warning. The status of blood pressure will be higher as the function of the body's organs decreases. Hypertension is an abnormal increase in blood pressure which is the main cause of cardiovascular disease. Objective: The purpose of this study was to describe the efforts of early detection of hypertension and prevention of hypertension in Kayu Bawang village in the working area of ​​Peat Public Health Center. Method: This type of research is quantitative with a descriptive research design. The population in this study were 150 respondents and a sample of 150 respondents, using a total sampling technique. Result: The results of this study are the results of measurements of systolic and diastolic blood pressure, the highest data is at Hypertension Level 1 (systolic 160-179 mmHg; diastolic 90-99 mmHg) as many as 46 respondents (30.7%). The results of early detection of hypertension with the highest data, namely being in early detection of hypertension is sufficient as many as 126 respondents (84%). The results of the prevention of hypertension with the highest data are in the prevention of hypertension enough as many as 120 respondents (80%). Conclusion: Therefore, the public must be able to detect early and make efforts to prevent hypertension so that the blood pressure of people with hypertension can be controlled